PERANAN DINAS PERHUBUNGAN DALAM MENYAMPAIKAN INFORMASI RUTE TRANS METRO DI KOTA PEKAN BARU - Axnur, Vico; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Delivery of Trans Metro Bus route information aims to make people aware and understand the existence of stop and Trans Metro Bus Route, so it can accept the existence of the Mass Public Transport Means and then motivate audiences to want to use the services of Trans Metro bus or switch from the usual use of private vehicles, be using the public transport services of Trans Metro Bus transportation as a means of transportation that can help them day to day activities The purpose of this study was to determine the role of the Department of Transportation Pekanbaru in providing information on Trans Metro Bus Route and the factors that hinder and support the delivery of such information .This study used a qualitative descriptive approach. Informants of this study was 4 People Pekanbaru City Department of Transportation employee, 1 stop officer, 4 people who have use the services of Trans Metro bus and 4 people who have never used the services of Trans Metro Bus services are selected using purposive sampling method and Accidental sampling. Types and sources of data consisting of primary data and secondary data. Data was collected by observation, interview and documentation. The technique of data analysis performed using data analysis and model Applebeum Anatol, and engineering data validity checking is done by the extension of participation, triangulation and checking membership.The results of this study indicate that the role performed in delivering Trans Metro Bus route information is in cooperation with the mass media and use interpersonal media, media groups, internet and outdoor media. The role is supporting factors such as the presence of a hot spot networks that facilitate employees in communicating with the public via the Internet. Then the Department of Transportation also has an official car for dissemination of information about Trans Metro Bus and Metro Bus Route Trans. Furthermore, the factors that hinder the role of the Department of Transportation which is the lack of information given by the government budget to support dissemination activities Trans Metro Bus Route. In operation, the amount of Trans Metro bus stop is still minimum, and also the distance between stops is also so far, it makes people become less likely to use the services of Trans Metro Bus.Keyword : Role, Trans metro route, Mass media, Interpersonal media, Media groups, Internet and outdoor media